Long‐term outcome of descemet membrane endothelial keratoplasty (DMEK) following failed penetrating keratoplasty (PK). Issue 7 (20th March 2020) - Schrittenlocher, Silvia; Schlereth, Simona L.; Siebelmann, Sebastian; Hayashi, Takahiko; Matthaei, Mario; Bachmann, Björn; Cursiefen, Claus
Abstract: Purpose: To assess the long‐term outcome of Descemet membrane endothelial keratoplasty (DMEK) following failed penetrating keratoplasty (PK). Methods: Retrospective review of 1840 consecutive DMEK surgeries from the prospective Cologne DMEK database performed between 07/2011 and 08/2017 at the Department of Ophthalmology, University of Cologne. Results: Fifty‐two eyes received a DMEK surgery after failed PK. Main indications for initial PK were Fuchs endothelial corneal dystrophy (23.1%), keratoconus and herpetic keratitis (each 15.4%). Best‐corrected visual acuity (BCVA) at 3, 6 and 12 months was 0.72 ± 0.39 ( n = 33), 0.56 ± 0.36 ( n = 32) and 0.38 ± 0.28 ( n = 23), respectively. Two‐ and 3‐year BCVA was 0.37 ± 0.21 ( n = 21) and 0.32 ± 0.18 ( n = 10). Mean improvement in visual outcome in logMAR lines was +4.3 ± 3.4 at 6 months, +5.0 ± 3.6 at 12 months, +6.0 ± 2.3 at 24 months and +5.4 ± 2.7 at 36 months, respectively. 59.6% received at least one rebubbling and 40.4% did not necessitate a rebubbling. Endothelial cell density (ECD)‐decrease at 6 months was 36% ( n = 17), 37% at 12 months ( n = 17), 40% at 2 years ( n = 8) and 32% at 3 years ( n = 2). 34.6% of transplants needed a regraft. Conclusion: Descemet membrane endothelial keratoplasty (DMEK) is a feasible treatment option after failed PK having a relatively good long‐term outcome.